Estudo sobre a ictiofauna do rio Sapucaí Mirim, afluente da margem esquerda do rio Grande no estado de São Paulo: composição, distribuição espacial e sazonalidade - Cesário, Vinícius Vendramini (2010)
The ichthyofauna of Sapucaí Mirim River, a tributary of Grande River at upper Paraná River was studied with a purpose on composition, seasonality and distribution environments. Samples were collected from June 2007 to June 2009. Different fishing gears were used to obtain samples: fine-mesh sieve, gill nets and cast nets of different mesh sizes and trawl. The results included the collection of 2,097 specimens belonging to 76 species of fish, divided into six Orders (Characiformes with 35 species, Siluriformes with 30, Perciformes with 5, Gymnotiformes with 3, Cyprinodontiformes with 2 and Synbranchiformes with one. The ichthyofauna composition showed slight dominance of Characiformes (46%) on Siluriformes (39%) and a high dominance of these two orders in relation to other orders: Perciformes (7%), Gymnotiformes (4%), Cyprinodontiformes (3%) and Synbranchiformes (1%). Defined a group of species listed among the main: Astyanax altiparanae, A. fasciatus, Steindachnerina insculpta, Leporinus friderici, Hypostomus ancistroides, Hypostomus strigaticeps, Hypostomus sp.1 and Rhamdia quelen. Defined a group of accessory species: Astyanax schubarti, Galeocharax knerii, Hoplosternum littorale, Hypostomus sp.2, Loricaria cf. lentiginosa, Schizodon nasutus and finally, a group of rare species: Bryconamericus sp., Leporinus striatus, Megalechis personata, Pimelodus sp., Pseudopimelodus mangurus, Salminus brasiliensis. Considerations on the preferred environment of the species in different sampling points and a comparison of the ichthyofauna Sapucaí Mirim River and the river Grande within the reservoir UHE Porto Colombia are presented here.